2018
DOI: 10.1128/jvi.00033-18
|View full text |Cite|
|
Sign up to set email alerts
|

Lactic Acid Downregulates Viral MicroRNA To Promote Epstein-Barr Virus-Immortalized B Lymphoblastic Cell Adhesion and Growth

Abstract: High plasma lactate is associated with poor prognosis of many malignancies, but its role in virally mediated cancer progression and underlying molecular mechanisms are unclear. Epstein-Barr virus (EBV), the first human oncogenic virus, causes several cancers, including B-cell lymphoma. Here, we report that lactate dehydrogenase A (LDH-A) expression and lactate production are elevated in EBV-immortalized B lymphoblastic cells, and lactic acid (LA; acidic lactate) at low concentration triggers EBV-infected B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…KSHV and EBV-negative (BJAB and DG75 from American Type Culture Collection [ATCC], Manassas, VA), KSHV-positive (BC3 and BCBL1 from ATCC) B-lymphoma cells, EBV-positive cells (B95.8 from ATCC and EBV-transformed primary B cell lines LCL in vitro generated in the lab[41]), iSLK (1mg/ml puromycin, 250ug/ml G418, a gift from Shou-Jiang Gao at University of South California) and iSLK-Bac16 (K-iSLK, 1mg/ml hygromycin, 250ug/ml G418 and 1ug/ml puromycin, a gift from Shou-Jiang Gao at University of South California) and iSLK.219 (400 μg/mL hygromycin, 250 μg/mL G418, and 4 μg/mL puromycin[42]) cells were maintained in DMEM medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin and streptomycin (Gibco-BRL). HUVEC (ATCC), and HEK293 (ATCC) cells, were maintained in DMEM supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…KSHV and EBV-negative (BJAB and DG75 from American Type Culture Collection [ATCC], Manassas, VA), KSHV-positive (BC3 and BCBL1 from ATCC) B-lymphoma cells, EBV-positive cells (B95.8 from ATCC and EBV-transformed primary B cell lines LCL in vitro generated in the lab[41]), iSLK (1mg/ml puromycin, 250ug/ml G418, a gift from Shou-Jiang Gao at University of South California) and iSLK-Bac16 (K-iSLK, 1mg/ml hygromycin, 250ug/ml G418 and 1ug/ml puromycin, a gift from Shou-Jiang Gao at University of South California) and iSLK.219 (400 μg/mL hygromycin, 250 μg/mL G418, and 4 μg/mL puromycin[42]) cells were maintained in DMEM medium supplemented with 10% fetal bovine serum (FBS) and 1% penicillin and streptomycin (Gibco-BRL). HUVEC (ATCC), and HEK293 (ATCC) cells, were maintained in DMEM supplemented with 10% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, the metabolic regulation of immune cells during health and disease has garnered increasing attention, as the active reconfiguration of immune cell metabolism enables these cells to maintain specific functions [56,57]. For instance, Mo et al found that lactic acid downregulates viral microRNA and promotes the growth of Epstein-Barr virus in immortalized B lymphocytes [58]. Moreover, we, as well as other groups, have found that CSFV infection can alter glycolysis in plasma and cells.…”
Section: Discussionmentioning
confidence: 59%
“…Previous studies also had noted the importance of LDH as an indicator of lung diseases. In a study on Epstein-Barr virus (EBV), researchers found that EBV infected B cells had more LDH transcripts than the uninfected B cells [ 12 ]. In addition, the serum levels of LDH increased in pneumocystis pneumonia (PcP) patients, probably was due to lung injury [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%